Prevalence and associated factors of non-communicable diseases among men: A cross-sectional analysis of Kenya Demographic and Health Survey 2022 data - John Baptist Asiimwe; Lilian Nuwabaine; Angella Namulema; Quraish Sserwanja; Joseph Kawuki; Grace Nambozi (PLoS ONE, 2026)
Background Non-communicable diseases (NCDs) are the leading cause of morbidity and mortality worldwide, with low- and middle-income countries (LMICs) increasingly being disproportionately affected. Although anecdotal evidence or reports indicate an increasing number of Kenyan men having NCDs, the prevalence and associated factors are not well understood. Therefore, this study aimed to determine the prevalence and associated factors of non-communicable diseases among men in Kenya. Methods Secondary data comprising 14,439 men aged 15–54 years from the 2022 cross-sectional Demographic and Health Survey (KDHS) in Kenya were analyzed using univariable and multivariable logistic regression analyses in SPSS, version 29. Results Overall, the percentage of men with at least one NCD was 9.4% (95% confidence interval [CI]: 8.7–10.2%). Whereas the proportion of participants with multiple NCDs was 1.9 (95% CI: 1.6–2.3). Across NCDs, the highest prevalent NCD was hypertension (3.5% 95%CI:3.1–3.9) followed by depression (2.2% (95%CI:1.9–2.5), anxiety (1.6% (95%CI:1.3–1.9), arthritis (1.4% (95%CI:1.1–1.6), heart disease (1.2% (95%CI:0.9–1.5), diabetes (1% (95%CI:0.8–1.3), lung disease (1% (95%CI:0.7–1.3), and cancer (0.1% (95%CI:0–0.1). In terms of multiple chronic conditions (multimorbidity), the majority of the participants had diabetes and hypertension (0.5% (95%CI:0.3–0.7) followed by hypertension and depression (0.3% (95%CI:0.2–0.4), hypertension and anxiety (0.3% (95%CI:0.2–0.4), and arthritis and depression (0.2% (95%CI:0.1–0.2). Several factors, such as age, region, residence, ethnicity, education level, health status, wealth index, religion, media access, and living a sedentary lifestyle, were found to be significantly associated with the prevalence of NCDs. Conclusion The overall prevalence of NCDs among men is relatively low based on available national data. We found that sociodemographic and lifestyle factors were significantly associated with the prevalence of NCDs. Although causal relationships cannot be inferred from this study, the findings suggest that initiatives such as tailored health education, regular medical checkups, and the promotion of physical activity may be relevant components of broader efforts to support men’s health in relation to non‑communicable diseases (NCDs). Region‑specific policies and culturally sensitive approaches may help address variations in risk factors and observed ethnic disparities. Encouraging healthier lifestyle practices among men of all backgrounds and improving access to integrated healthcare in rural areas may also be important considerations. Further research is needed to explore how media exposure, media content, health messaging, and religious contexts may influence men’s exposure to NCDs in Kenya and other sub-Saharan countries.